LAND USE PLANNING FOR BEEKEEPING USING GEOGRAPHIC INFORMATION SYSTEM IN SUKABUMI REGENCY, WEST JAVA - Varian Triantomo; Widiatmaka Widiatmaka; Asnath Maria Fuah (Graduate School Bogor Agricultural University (SPs IPB), 2016)
Beekeeping is one of the alternative businesses that can be developed without converting the existing land use. Deveoping the business of beekeeping should consider the biophysically suitable area for bees themselves and also for the bee forage availability. The objective of this study was to provide the direction of development area for beekeeping. The methods used consist ofa combination of remote sensing, geographic information system, and analytical hierarchy process. The recommended area for beekeeping in Sukabumi regency consists of two areas: forest and dry land agriculture area. The protected area has two priorities: The first priority area for beekeeping is 3,335.52 ha (6.4%), while second priority is 48,415.22 ha (93.6%) that covered 14 sub-districts. The cultivation area has three priorities: First priority area is 1,163.92 ha, second priorityarea is 6,044.98 ha, and third priority area is 2,651.21 ha that covered 9 sub-districts. Based on result of analysis with the existing beekeeping in Sukabumi regency, local government of Sukabumi regency or local farmer could develop program for beekeeping in such as sub district: Cibadak, Cicurug, Cidahu, Ciemas, Cikidang, Ciracap, Cisolok, Kabandungan, Kadudampit, Kalapanunggal, Nagrak, Pelabuhan Ratu, Sukabumi, Sukaraja, Jampang Kulon, Pabuaran, Sagaranten, Surade, and Tegalbuleud.